Halal Branding Strategy: The Impact of Halal Labeling and Endorsement - Wulan Saraswati; Siti Asiyah; Muhammad Ridwan Basalamah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study aims to analyse the influence of celebrity endorsement and halal labelling on Wardah cosmetics purchase decisions, with brand image serving as a mediating variable. This research addresses the limitations of previous studies, which generally examined celebrity promotion and halal legitimacy separately, thereby failing to comprehensively explain how both factors shape the purchasing behaviour of Muslim consumers. The novelty of this study lies in integrating promotional attractiveness and halal legitimacy into a unified consumer behaviour model within the context of halal branding and Islamic marketing. This study employed an explanatory quantitative approach involving Wardah consumers in Malang City selected through purposive sampling. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that celebrity endorsement did not significantly influence purchase decisions, either directly or indirectly through brand image. In contrast, halal labelling demonstrated a strong influence on both purchase decisions and brand image. Brand image also contributed positively to purchase decisions and mediated the relationship between halal labelling and purchasing behaviour. These findings confirm that Muslim consumers’ purchasing decisions are driven more by halal credibility than by the attractiveness of celebrity figures. Therefore, halal labelling functions not only as a certification marker but also as a source of trust, brand legitimacy, and competitive differentiation in the halal cosmetics industry.